Preparation method and application of efficient and stable low-coordination C-coordination Ni monatomic catalyst

By forming a C-coordinated low-coordinated Ni single-atom catalyst (L-Ni-NC-C) within a carbon substrate, the challenges of CO2RR catalysts in activation of CO2 and optimization of CO selectivity are solved, achieving efficient CO generation and long-term stability.

CN119657201AActive Publication Date: 2025-03-21ANHUI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411923197.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-21
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Existing CO2RR catalysts have challenges in efficient activation of CO2 and optimizing CO selectivity, especially due to the lack of electrons in high-priced Ni and the strong feedback π bond between metal Ni sites and *CO.

Method used

By inducing local charge distribution within the carbon substrate, a C-coordinated low-coordinated Ni single-atom catalyst (L-Ni-NC-C) is formed, which achieves high current density, ultra-high CO selectivity and stability in H-type electrolytic cells and gas diffusion flow cells.

Benefits of technology

The effective adsorption of *COOH and subsequent desorption of *CO during CO2RR are achieved, which significantly improves the CO generation rate and selectivity, and also has industrial-grade current density and long-term stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657201A_ABST
    Figure CN119657201A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of carbon dioxide reduction catalytic materials, and discloses a preparation method and application of an efficient and stable low-coordination C-coordinated Ni monatomic catalyst, and the catalyst with a unique low-coordination structure (Ni-SACs are co-coordinated with two C atoms and one N atom in a carbon matrix) is synthesized through a simple two-step method. And the undersaturated coordination structure has dual functions in CO2RR, so that the adsorption of * COOH is enhanced, and the subsequent desorption of * CO is promoted, thereby effectively promoting the CO2RR process. The preparation process is simple, low in cost, good in repeatability, suitable for large-scale industrial production, capable of stably operating under the industrial current density and high in selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of nanocatalytic materials, and specifically relates to a method for preparing a novel, highly efficient and stable low-coordinated nickel single-atom electrocatalyst and its application in electrocatalytic carbon dioxide reduction catalysis. Background Art

[0002] The electrochemical carbon dioxide reduction reaction (CO2RR) is a highly promising carbon recycling technology that uses renewable electricity to convert CO2, a large amount of greenhouse gas produced by burning fossil fuels, into more valuable carbon chemicals and fuels while mitigating climate hazards. Among various CO2RR pathways, the production of CO has significant advantages. CO plays a key role as a primary chemical feedstock and intermediate in many industrial production processes, especially in Fischer-Tropsch synthesis, where it can be further purified to higher-value products such as diesel. However, the CO2RR process is affected by the high activation energy barrier of CO2 molecules and the occurrence of multiple competing reactions. Efficient electrocatalysts are crucial to improve the CO2RR performance, enabling high generation rates and optimized selectivity. Although noble metals such as Au and Ag have excellent electrocatalytic performance for CO2RR to CO, their high price and scarcity limit their widespread commercial application. Therefore, there is an urgent need to develop cost-effective catalysts that can achieve industrial-grade current density while maintaining excellent CO selectivity over a wide potential window.

[0003] Transition metals (TMs) abundant in the Earth's crust, such as Fe, Co, and Ni, have unique electronic structures with tunable d orbitals and abundant outer d electrons. Notably, the d electrons on these metals can interact with the outer molecular orbitals of adsorbed CO molecules, causing structural bending and charge rearrangement, thereby promoting CO activation. For Ni-based catalysts, the conversion of CO to CO during CO2RR is usually governed by the trade-off between *COOH adsorption and *CO desorption. Specifically, the high-valent Ni cannot provide sufficient electrons for CO2 activation and subsequent *COOH adsorption. In contrast, the electron-rich metallic Ni sites exhibit extremely strong feedback π bonds with *CO, thereby hindering its desorption. A reliable approach is to anchor and stabilize these TM sites by ligands in the substrate, which provide a significant stabilization effect through strong metal-support interactions. In addition, single-atom catalysts (SACs) have the maximum utilization of TM atoms, further establishing their extremely high potential as cost-effective catalysts for CO2RR with excellent activity and remarkable stability.

[0004] Currently, TM-SACs have been extensively studied for CO2RR, mainly focusing on TM-N4-C catalysts. However, the symmetrical coordination environment and high electronegativity of the N atom may lead to insufficient adsorption strength of the key *COOH intermediate, thus limiting the CO production rate. By adjusting the coordination structure of the metal active center, the binding energy can be deeply optimized. Therefore, designing low-coordinated TM-SACs to replace N coordination with C coordination has high potential, but there are still challenges in achieving precise synthesis. Summary of the invention

[0005] In order to balance the adsorption of *COOH and the desorption of *CO during the CO2RR process, the present invention provides a preparation method and application of a novel undersaturated carbon-coordinated Ni single-atom electrocatalyst that achieves high current density, ultra-high CO selectivity and remarkable stability in both H-type electrolytic cells and gas diffusion flow cells. The present invention finds that the carbon defects inherent in the carbon substrate can induce local charge distribution in graphite, enhance the anchoring of TM atoms, and thus help form C-coordinated TM sites. TM atoms may be partially reduced and spontaneously captured by newly generated carbon defects, accompanied by the elimination of N anchoring sites, thereby realizing low-coordinated TM-SACs with C coordination.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme:

[0007] A method for preparing an efficient and stable low-coordinated C-coordinated Ni single-atom catalyst comprises the following steps:

[0008] Step 1: Pour the methanol solution containing Zn(NO3)2·6H2O and Ni(acac)2 into the methanol containing 2-methylimidazole, stir evenly, age at room temperature, collect the white precipitate, wash with methanol, and dry to obtain the reaction precursor Ni-ZIF-8 nanoparticles. Preferably, the dosage ratio of Zn(NO3)2·6H2O, Ni(acac)2 and 2-methylimidazole is 1.0-1.3:0.11-0.55:1.2-1.5, and the room temperature aging time is 8-12 hours. The drying is carried out in an oven at 60-80°C for 6-12 hours.

[0009] Step 2, annealing the Ni-ZIF-8 nanoparticles in a N2 atmosphere, then etching the resulting black powder and drying. Preferably, the annealing temperature is 750-850°C and the time is 0.5-2h. The etching is to soak the annealed Ni-ZIF-8 nanoparticles in a 0.5-1M H2SO4 solution for 3-5h. The drying is to dry in an oven at 60-80°C for 24-36h.

[0010] Step 3: heat-treat the product obtained in step 2 in an NH3 atmosphere to obtain a low-coordinated C-coordinated Ni single-atom catalyst, named L-Ni-NC-C. Preferably, the heat treatment temperature is 850-950°C and the time is 1-2 hours.

[0011] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0012] The present invention synthesizes a low-coordinated C-coordinated Ni single-atom catalyst by a simple two-step method. The obtained catalyst has a unique low-coordinated structure (Ni-SACs is co-coordinated with two C atoms and one N atom in the carbon matrix). The undersaturated coordination structure in L-Ni-NC-C has a dual function in CO2RR, which not only enhances the adsorption of *COOH, but also promotes the subsequent desorption of *CO, thereby effectively promoting the CO2RR process. The preparation process of the present invention is simple, low-cost, and has good repeatability. It is suitable for large-scale industrial production, can operate stably at industrial current density, and has high selectivity. The present invention proposes an innovative strategy for optimizing the coordination structure of the catalyst, which can effectively promote the development of the next generation of electrocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a scanning electron microscope image of the L-Ni-NC-C electrocatalyst obtained in Example 1.

[0014] Figure 2 This is a transmission electron microscopy image of the L-Ni-NC-C electrocatalyst obtained in Example 1.

[0015] Figure 3 This is a double spherical aberration corrected transmission electron microscopy image of the L-Ni-NC-C electrocatalyst obtained in Example 1.

[0016] Figure 4 This is the X-ray diffraction pattern of the L-Ni-NC-C electrocatalyst obtained in Example 1.

[0017] Figure 5 FE of the materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 in 0.1M KHCO3 solution in an H-type electrolytic cell CO Performance curves.

[0018] Figure 6 The current density and FE of the L-Ni-NC-C electrocatalyst obtained in Example 1 in a 0.1M KHCO3 solution in an H-type electrolytic cell at a constant voltage of -0.9V vs. RHE CO Curve of changes over time.

[0019] Figure 7The Faraday efficiency FE of the L-Ni-NC-C electrocatalyst obtained in Example 1 at different current densities in an alkaline electrolyte (1 mol / L KOH) in a gas diffusion flow cell CO And the current density diagram of CO.

[0020] Figure 8 This is a curve showing the change in voltage over time of the L-Ni-NC-C electrocatalyst obtained in Example 1 at a constant current density in an alkaline electrolyte (1 mol / L KOH) in a gas diffusion flow cell.

[0021] Fig. 9 The Faraday efficiency FE of the L-Ni-NC-C electrocatalyst obtained in Example 1 at different current densities in a gas diffusion flow cell neutral electrolyte (1 mol / L KHCO3) CO And the current density diagram of CO.

[0022] Fig.10 This is a curve showing the voltage variation over time of the L-Ni-NC-C electrocatalyst obtained in Example 1 at a constant current density in a neutral electrolyte (1 mol / L KHCO3) in a gas diffusion flow cell. DETAILED DESCRIPTION

[0023] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0024] Example 1

[0025] In this example, the L-Ni-NC-C electrocatalyst was prepared according to the following steps:

[0026] Step 1: Add 1.19g Zn(NO3)2·6H2O(AR), 0.11g Ni(acac)2(AR) and 30mL methanol(AR) to the first beaker and stir evenly; add 1.32g 2-methylimidazole(AR) and 15mL methanol(AR) to the second beaker and stir evenly. Pour the solution in the first beaker into the second beaker, stir evenly at room temperature, and then age at room temperature for 12h. The obtained product is centrifuged (centrifugal speed is 9800rpm, centrifugal time is 3min), washed with methanol 3 times, and then dried in a 60℃ oven for 6h to obtain the reaction precursor Ni-ZIF-8 nanoparticles.

[0027] Step 2: Anneal the Ni-ZIF-8 nanoparticles obtained in step 1 in a nitrogen atmosphere at 800°C for 0.5 h. After cooling to room temperature, immerse and etch the obtained black powder in a 0.5M H2SO4 solution for 3 h, and then dry the product in an oven at 60°C for 24 h.

[0028] Step 3: heat-treat the product obtained in step 2 at 950° C. in an NH 3 atmosphere for 1 h, and wait until the temperature drops to room temperature to obtain the L-Ni-NC-C electrocatalyst.

[0029] The scanning electron microscope image and transmission electron microscope image of the L-Ni-NC-C electrocatalyst prepared in this example are shown in FIG. Figure 1 , Figure 2 As shown, it can be seen that the obtained product has a rhombic dodecahedral structure and is of uniform size, with a particle size of about 200 nm.

[0030] The double spherical aberration corrected transmission electron microscopy image and X-ray diffraction image of the L-Ni-NC-C electrocatalyst prepared in this example are shown in Figure 3 , Figure 4 As shown. Figure 3 It can be observed that the nickel atoms in the product obtained in this example are dispersed at the atomic level. Figure 4 It can be observed that the L-Ni-NC-C electrocatalyst shows two main diffraction peaks at 26.1° and 43.8°, corresponding to the (002) and (101) characteristic peaks of graphite, respectively. These broad and weak peaks indicate that the graphitic carbon structure is less graphitized and rich in defects, which can promote the anchoring and stabilization of single Ni atoms. L-Ni-NC-C does not show any additional diffraction peaks related to metallic Ni, further confirming the atomic dispersion of Ni atoms in the carbon matrix.

[0031] The electrochemical performance of the L-Ni-NC-C electrocatalyst obtained in this example was tested using a three-electrode system:

[0032] 6.25 mg of the electrocatalyst was added to a mixed solvent containing 15 μL of Nafion D-520 dispersed aqueous solution, 165 μL of water and 320 μL of isopropanol, and then the mixture was oscillated and ultrasonicated until it was uniformly dispersed to obtain black ink.

[0033] First, in the test of the H-type electrolytic cell, 80 μL of the prepared dispersed ink was dropped on carbon paper and dried naturally to participate in the test as a working electrode. The reference electrode was an Ag / AgCl electrode, the counter electrode was a Pt mesh electrode, and the electrolyte solution was a 0.1 mol / L KHCO3 solution. The electrochemical performance Faraday efficiency (FE) test of the L-Ni-NC-C electrocatalyst was carried out using step potential electrolysis with an applied potential range of -0.4 to -1.2 V vs. RHE, and a gas chromatograph was used to monitor the gas products online. FE CO The size indicates the electrocatalytic performance, FE CO The larger the value and the closer it is to 100%, the better the performance. The L-Ni-NC-C electrocatalyst was tested for constant voltage stability. As time goes by, the corresponding current decreases, and FE CO Decline.CO and the current reduction indicates stability, FE CO The larger it is, the less the current drops, indicating better stability.

[0034] The FE of the L-Ni-NC-C electrocatalyst obtained in this example in 0.1M KHCO3 solution of H-type electrolytic cell CO Performance as Figure 5 and Figure 6 As shown, the sample of Comparative Example 1 (Ni-NC) and the sample of Comparative Example 2 (Ni-NPs) are used as comparative catalysts. Figure 5 It can be seen that the L-Ni-NC-C electrocatalyst prepared in this example has a wide potential window of -0.5V to -1.1V relative to the reversible hydrogen electrode (vs. RHE), FE CO Continuously exceeded 97%, FE CO At -0.7V vs. RHE, it reached an extremely high 99.1%. Compared with the samples of comparative sample 1 and comparative sample 2, the catalytic activity was significantly improved. Figure 6 It can be seen that L-Ni-NC-C still maintains a selectivity of more than 96% after continuous operation at -0.9 V vs. RHE for 50 h, and the catalytic activity has hardly changed, demonstrating the excellent stability of the L-Ni-NC-C electrocatalyst.

[0035] In order to further prove whether the nickel single atom catalyst obtained in this example can be used in industrial current to better meet industrial requirements, the catalyst was placed in a gas diffusion flow electrolysis cell, and the electrolyte solution was alkaline (1 mol / L KOH solution) or neutral (1 mol / L KHCO3 solution). Then a constant large current (industrial current density) was applied to it to carry out constant current Faraday efficiency (FE) test and constant current stability test.

[0036] like Figure 7 As shown in Figure 2, the L-Ni-NC-C catalyst exhibited very high selectivity for CO formation under alkaline conditions (1 mol / L KOH), with a CO conversion range of 50 to 300 mA cm -2 Within the total current density range, FE CO Reach more than 99%. Figure 8 The long-term durability test shows that L-Ni-NC-C has strong stability. Within 24h, FE CO Always over 99%, potential voltage fluctuations are basically negligible.

[0037] In addition to the commonly used alkaline conditions, neutral electrolytes (1 mol / L KHCO3) were also used for testing, such as Fig. 9 As shown, L-Ni-NC-C has a high conductivity in the range of 50 to 400 mA cm -2A very high FE is achieved within a very wide current density range CO , more than 99%. Fig.10 In the gas diffusion flow cell, the L-Ni-NC-C was evaluated in a neutral electrolyte at 250 mA cm -2 Stability at industrial current density, FE CO The sustained voltage was over 99% within 10 h with little voltage fluctuation, which indicated the excellent stability of L-Ni-NC-C.

[0038] Figure 7-10 The results show that L-Ni-NC-C has a large current density, ultra-high FE under both alkaline and neutral conditions. CO The selectivity and good stability highlight its great potential and broad prospects for practical applications.

[0039] Comparative Example 1

[0040] This comparative example prepared Ni-NC nickel single atom electrocatalyst according to the following steps:

[0041] Step 1: Add 1.19g Zn(NO3)2·6H2O(AR), 0.11g Ni(acac)2(AR) and 30mL methanol(AR) to the first beaker and stir evenly; add 1.32g 2-methylimidazole(AR) and 15mL methanol(AR) to the second beaker and stir evenly. Pour the solution in the first beaker into the second beaker, stir evenly at room temperature, and then age at room temperature for 12h. The obtained product is centrifuged (centrifugal speed is 9800rpm, centrifugal time is 3min), washed with methanol 3 times, and then dried in a 60℃ oven for 6h to obtain the reaction precursor Ni-ZIF-8 nanoparticles.

[0042] Step 2: Anneal the Ni-ZIF-8 nanoparticles obtained in step 1 in a nitrogen atmosphere at 800°C for 0.5 h. After cooling to room temperature, immerse and etch the obtained black powder in a 0.5M H2SO4 solution for 3 h, and then dry the product in an oven at 60°C for 24 h.

[0043] Step 3: heat-treat the product obtained in step 2 at 950° C. for 1 h in an Ar atmosphere, and wait until the temperature drops to room temperature to obtain a Ni single-atom catalyst, named Ni-NC. The product obtained in this comparative example is atomically dispersed.

[0044] The electrochemical performance of the nickel single-atom electrocatalyst obtained in this comparative example was tested in the same manner as in Example 1. The results showed that the Ni-NC electrocatalyst prepared in this comparative example had a FE of 1.04 W / m2 in an H-type electrolytic cell. CO The maximum is 86.1%.

[0045] Comparative Example 2

[0046] This comparative example prepared Ni-NPs nickel single atom electrocatalyst according to the following steps:

[0047] Step 1: Add 1.19g Zn(NO3)2·6H2O(AR), 0.55g Ni(acac)2(AR) and 30mL methanol(AR) to the first beaker and stir evenly; add 1.32g 2-methylimidazole(AR) and 15mL methanol(AR) to the second beaker and stir evenly. Pour the solution in the first beaker into the second beaker, stir evenly at room temperature, and then age at room temperature for 12h. The obtained product is centrifuged (centrifugal speed is 9800rpm, centrifugal time is 3min), washed with methanol 3 times, and then dried in a 60℃ oven for 6h to obtain the reaction precursor Ni-ZIF-8 nanoparticles.

[0048] Step 2: Anneal the Ni-ZIF-8 nanoparticles obtained in step 1 in a nitrogen atmosphere at 800°C for 0.5 h. After cooling to room temperature, immerse and etch the obtained black powder in a 0.5M H2SO4 solution for 3 h, and then dry the product in an oven at 60°C for 24 h.

[0049] Step 3: Heat-treat the product obtained in step 2 at 950° C. for 1 h in an NH 3 atmosphere, and wait until the temperature drops to room temperature to obtain a Ni nanoparticle electrocatalyst, named Ni-NPs. The product obtained in this comparative example is nickel nanoparticles.

[0050] The electrochemical performance of the Ni-NPs electrocatalyst obtained in this comparative example was tested in the same manner as in Example 1. The results showed that the Ni-NPs electrocatalyst obtained in this comparative example had a FE of 1.04 W / m2 in the H-type electrolytic cell. CO The maximum is 88.8%.

[0051] The above is only an exemplary embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention shall be implemented according to the conventional means in the art unless otherwise specified and limited.

Claims

1. A method for preparing an efficient and stable low-coordinated C-coordinated Ni single-atom catalyst, characterized in that: The steps include: Step 1, pouring a methanol solution containing Zn(NO3)2·6H2O and Ni(acac)2 into methanol containing 2-methylimidazole, stirring evenly, aging at room temperature, collecting white precipitates, washing and drying, and obtaining reaction precursor Ni-ZIF-8 nanoparticles; Step 2, annealing the Ni-ZIF-8 nanoparticles in a N2 atmosphere, then etching the resulting black powder and drying it; Step 3: heat-treat the product obtained in step 2 in an NH3 atmosphere to obtain a low-coordinated C-coordinated Ni single-atom catalyst, named L-Ni-NC-C.

2. The preparation method according to claim 1, characterized in that: In step 1, the usage ratio of Zn(NO3)2·6H2O, Ni(acac)2 and 2-methylimidazole is 1.0-1.3:0.11-0.55:1.2-1.

5.

3. The preparation method according to claim 1, characterized in that: In step 1, the room temperature aging time is 8 to 12 hours.

4. The preparation method according to claim 1, characterized in that: In step 2, the annealing temperature is 750-850° C. and the time is 0.5-2 h.

5. The preparation method according to claim 1, characterized in that: In step 2, the etching is performed by immersing the annealed Ni-ZIF-8 nanoparticles in a 0.5-1M H2SO4 solution for 3-5 hours.

6. The preparation method according to claim 1, characterized in that: In step 3, the heat treatment temperature is 850-950° C. and the time is 1-2 hours.

7. A low-coordinated C-coordinated Ni single-atom catalyst prepared by the preparation method described in any one of claims 1 to 6.

8. Use of the low-coordinated C-coordinated Ni single-atom catalyst according to claim 7 as a catalyst in an electrochemical carbon dioxide reduction reaction.

Citation Information

Patent Citations

  • Ni-N-C catalyst for electroreduction reaction of carbon dioxide and preparation and application thereof

    CN109652821A

  • Supported monatomic metal catalyst and preparation method and application thereof

    CN111036261A

  • Preparation method and application of carbon material rich in topological defects obtained through high-temperature ammonia treatment

    CN112830468A

  • Preparation method of novel carbon-based material loaded transition metal monatomic catalyst

    CN112973754A

  • Monatomic catalyst for electrochemical reduction of carbon dioxide and preparation method thereof

    CN114214642A